Analysis of Mathematics Problem Solving Ability Viewed from Self-Regulated Learning - Haqiqiyah, Arina; Putri, Rani Kurnia (Indonesian Journal of Education and Mathematical Science, 2025)
The goal of this study was to assess SMA Wachid Hasyim 5 Surabaya students' abilities to solve arithmetic problems in the low, medium, and high self-regulated learning categories. Three students from class X IPA 3 participated in this qualitative study. Data for this study were gathered by questionnaires, tests, and interviews and analyzed through data reduction, data presentation, and drawing conclusions. The authenticity of the data in this investigation was determined via time triangulation. Based on the findings and discussion, the researcher concluded that the four steps of problem solving for students with high and moderate independence when learning can be fulfilled properly; however, independent students are experiencing difficulties at the stage of carrying out the settlement plan because students are not careful about the results of their calculations. Meanwhile, students with low learning independence meet one of the indications, namely understanding the problem, but are unable to appropriately put down what is learned in the questions, resulting in incorrect calculations.